The Potential for Corporate Corruption in Mining Licensing Policies for Religious Organizations in Indonesia - Erma Rusdiana; Lindra Darnela; Muwaffiq Jufri; Paul Atagamen Aidonojie; Souad Ezzerouali (Lex Scientia Law Review, 2025)
The primary purpose of this research is to examine the potential corruption by corporations through the policy of granting mining licenses to religious community organizations (religious organizations) in Indonesia. This research contributes to analysing the potency of corruption and provides a concept for preventing corruption in the mining sector after the issuance of mining business licenses for religious organizations. The novelty of this research is to detect various potential criminal acts of corruption by corporations after the enactment of regulations that permit religious organizations to manage mines. Additionally, the concept of corporate corruption prevention provides policy input to prevent corruption in this sector. This research uses normative legal research methods with conceptual, statutory, and case approaches. A significant finding of this research is that corruption is potentially liable in mining management by religious organizations, considering that the business entities owned by religious organizations are not very credible in managing the mining sector. Furthermore, previous studies and surveys have found that many mining companies overlook or ignore their anti-corruption commitments and policies. The potency of corruption is also exacerbated by regulatory loopholes in the mining sector, which are susceptible to corruption. This research recommends a policy that regulates the standard quality of the business entity owned by a religious organization, especially human resources capacity, organizational management, and anti-corruption commitments and policies within the business entity. In addition, to avoid potential corruption in this sector, the government's commitment and the participation of society in monitoring mining governance are certainly needed.